The effect of hemispheric epileptic focuses on the autonomic nervous system in epileptic patients - Berilgen, M. S.; Tekatas, A.; Bulut, S.; Mungen, B.; Demir, C. F. (Wiley-Blackwell, 2010)
[Abstract Not Available]
14th Congress of European-Federation-of-Neurological-Societies -- SEP, 2010 -- Geneva, SWITZERLAND